Big Data and Academic Profession Studies: Toward a New Research Agenda - Kweik, Marek (International Higher Education, 2025)
<h3 id="the-keyword-for-the-future-of-academic-profession-studies-is-complementarity-insights-from-surveys-whether-large–or-small-scale-differ-fundamentally-from-those-from-interviewsbut-together-they-can-advance-the-field-both-theoretically-and-empirically-big-data-should-therefore-complement-surveys-and-interviews-while-macro-level-analyses-should-accompany-micro-level-studies" data-pm-slice="1 1 []">The keyword for the future of academic profession studies is complementarity. Insights from surveys, whether large- or small-scale, differ fundamentally from those from interviews—but together, they can advance the field both theoretically and empirically. Big data should therefore complement surveys and interviews, while macro-level analyses should accompany micro-level studies.